2020
DOI: 10.1155/2020/4729019
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Expression Level of LncRNA Malat1 in Diabetic Kidney Disease Patients and Its Clinical Significance

Abstract: Background. Long noncoding RNA MALAT1 is closely related to diabetes and kidney diseases and is expected to be a new target for the diagnosis and treatment of diabetic nephropathy. Objective. This study aimed to explore the circulating expression level and significance of lncRNA Malat1 in patients with type 2 diabetes mellitus (T2DM) and diabetic kidney disease (DKD). Methods. Quantitative real-time PCR (qPCR) was conducted to assess the expression of lncRNA Malat1 in 20 T2DM patients, 27 DKD patients, and 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Metastasis-associated lung adenocarcinoma transcript 1, also known as Neat2 (Malat1) is one of the most analyzed lncRNAs in DKD samples. The qualitative analysis showed that lncRNAs were expressed in serum, urine, peripheral blood mononuclear cells, and kidney tissue [ 29 , 30 , 36 , 37 , 39 ]. There were increased expressions of lncRNA MALAT1 in DKD, translocation of β -catenin to the nucleus, enhanced expressions of MALAT1 connexin serine/arginine splicing factor 1 (SRSF1), and expressions of p-cadherin and tight junction protein ZO-1.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis-associated lung adenocarcinoma transcript 1, also known as Neat2 (Malat1) is one of the most analyzed lncRNAs in DKD samples. The qualitative analysis showed that lncRNAs were expressed in serum, urine, peripheral blood mononuclear cells, and kidney tissue [ 29 , 30 , 36 , 37 , 39 ]. There were increased expressions of lncRNA MALAT1 in DKD, translocation of β -catenin to the nucleus, enhanced expressions of MALAT1 connexin serine/arginine splicing factor 1 (SRSF1), and expressions of p-cadherin and tight junction protein ZO-1.…”
Section: Discussionmentioning
confidence: 99%
“…The association of MALAT1 with inflammatory factors has been shown in various studies [ 37 , 38 , 39 ]. Different studies have shown that MALAT1 expression is increased in diabetes-related complications, including diabetic cardiomyopathy, diabetic kidney disease, diabetic retinopathy, and gestational diabetes [ 40 , 41 , 42 , 43 , 44 ]. Hu et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, circulating long noncoding RNA DKFZP434I0714 was reported to predict adverse cardiovascular outcomes in patients with end-stage renal disease [19]. Circulating lncRNA Malat1 was found to be highly expressed in diabetic nephropathy patients, which is expected to be a new target for the diagnosis of diabetic nephropathy [20]. More and more lncRNAs in CKD remain to be characterized, and systematic pro ling of lncRNAassociated ceRNA network analysis is needed to identify hub genes and reveal the regulatory mechanisms involved in the pathogenesis of CKD.…”
Section: Discussionmentioning
confidence: 99%